Balanço tendencial das dissertações e teses defendidas no PEPG em Educação: História, Política, Sociedade - PUC/SP (1973/2019) - Silva, Tatiane Diniz da (2021)
This research, through a trend balance of the academic production of the PEPG in Education: History, Politics, Society (PUC-SP), expressed by the dissertations and thesis defended between 1973-2019, aimed to analyze this production in order to reveal its singularities and approaches according to the different periods, expressed by the structural changes that occurred, based on the contributions of the theoretical framework of cultural materialism (Williams, 1979, 1980), which allowed us to understand the material production of this literature as an expression of the contexts in which they were produced. Therefore, an exhaustive survey of this production was carried out in the database of the Nadir Gouvêa Kfouri Library, of the Pontifical Catholic University of São Paulo, which resulted in the elaboration of an Excel matrix spreadsheet, composed by 1224 works, containing the following indicators: academic structure, field of knowledge, level of production (dissertation or thesis), supervisor, general theme and specific theme. Later, these data were exported to the Sphinx iQ2 statistical treatment software, for the production of tables and graphics that made it possible to compare this production over its fifty years of existence. The main findings were the changes in themes followed the changes in the academic-curricular structure that occurred and, due to the small number of professors, the close relationship, almost always, between productions within a thematic focus with only one teacher